EXPLORING MULTIMEDIA METHODS FOR DIAGNOSING MATHEMATICAL CONCEPT FORMATION: A METHODOLOGICAL FRAMEWORK - Radjapov Komil Askarovich (Western European Studies, 2024)
This paper presents a methodological framework for utilizing multimedia technologies in diagnosing the formation of mathematical concepts. As technology becomes increasingly integrated into education, particularly in mathematics instruction, the need for effective diagnostic tools becomes paramount. The proposed framework aims to address this need by leveraging multimedia tools to assess students' comprehension and application of mathematical concepts.
Keywords: Multimedia technologies; mathematical concept formation; diagnostic tasks